2021
DOI: 10.1108/ijoem-07-2020-0831
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional and hierarchical model of banking services and behavioral intentions of customers

Abstract: PurposeBanking services encounter major challenges in determining customer's psychometric behavioral intentions. Scholars suggest that a theoretical approach to better understand the key constructs of service marketing, such as service quality, perceived value, customer satisfaction, corporate image and behavioral intentions, is critical to bank performance. The present study aims to design and test a comprehensive multidimensional and hierarchical model of service quality with higher-order psychometric constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 57 publications
2
32
2
Order By: Relevance
“…Results show that atmosphere negatively moderates the mediation between SSTs perception and FLEs perception; in other words, a favourable perception of the service atmosphere diminishes the mediating role of employees. On the one hand, this finding corroborates insights of marketing research (e.g., Elmashhara & Soares, 2022 ; Roggeveen et al, 2020 ; Turley & Milliman, 2000 ); and of consumer research set in retail banking (e.g., Bakar et al, 2017 ; Hossain et al, 2021 ) establishing the key role of atmosphere in shaping consumer perceptions; on the other hand, it encourages some reflections about the specific role of atmospherics in retail banking. The retail banking sector is undergoing deep transformations, deeply influenced by technological evolution, and pushed even more forward by the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Results show that atmosphere negatively moderates the mediation between SSTs perception and FLEs perception; in other words, a favourable perception of the service atmosphere diminishes the mediating role of employees. On the one hand, this finding corroborates insights of marketing research (e.g., Elmashhara & Soares, 2022 ; Roggeveen et al, 2020 ; Turley & Milliman, 2000 ); and of consumer research set in retail banking (e.g., Bakar et al, 2017 ; Hossain et al, 2021 ) establishing the key role of atmosphere in shaping consumer perceptions; on the other hand, it encourages some reflections about the specific role of atmospherics in retail banking. The retail banking sector is undergoing deep transformations, deeply influenced by technological evolution, and pushed even more forward by the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 76%
“…In other words, to redefine their value proposition in the market, players may be urged to refocus the role of bank branches, which, rather than being seen as a liability, may instead hold an enormous strategic potential. Operating branches in which technology is not dominating the service environment, rather it is fully integrated in it, may allow banks to attract diverse customer segments (e.g., customers more or less accustomed to technology usage); furthermore, by creating a pleasant atmosphere, banks may succeed ensuring those customers perceptions that are key for the overall customer evaluations of the service (e.g., Bakar et al, 2017 ; Hossain et al, 2021 ). Notably, a pleasant environment may not just improve the overall customer evaluation, rather it may also work as a relief for customers, on the one hand encouraging them to experiment technology; on the other hand, allowing banks to release more human resources and focus them on more value-added tasks, like personal consultancy.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [34] studies the link between service justice, service quality, social influence, image with customer satisfaction and loyalty, and the moderating impact of ownership in the banking sector in Bangladesh. They found that service justice, service quality, and social influence are directly linked to customer loyalty.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Technological innovation has made people more aware of what is going on in the world, especially in a service context [1]. However, COVID-19 is pushing banks to find more efficient service atmospheres due to the irregular buying patterns of customers [2]. The COVID-19 pandemic has created rumors and anxieties among customers that drastically affect their financial decisions and can impact their preand postadoption behavior, including satisfaction, patronage behavior, and word-of-mouth approach [3].…”
Section: Introductionmentioning
confidence: 99%
“…Customers tend to rate their experiences with respect to price fairness, which is likely to impact service perceptions and overall satisfaction. Thereby, an efficient service with reasonable prices becomes inevitable in achieving customer satisfaction and long-term buyer-customer relationships [2]. A substantial body of prior research has documented that instrumental and distributive justice have a significant positive influence on bank client satisfaction and behavioral intentions [6], while service quality is treated as a strategic weapon in the battle to achieve perfection in overall service accomplishment [7].…”
Section: Introductionmentioning
confidence: 99%